(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article provides data about Veronica L. rarity plants in flower bad recommended for landscaping in the valleys districts of Kyrgyzstan.